PEOPLE'S ECONOMIC EMPOWERMENT BASED ON QUR'ANIC VALUES: Efforts to Foster a Spirit of Independence and Entrepreunership in the Modern Era - Safrudin; Muhammad Saman (Sekolah Tinggi Ilmu Ushuluddin (STIU) Darul Hikmah, 2023)
Poverty and inequality of social strata in Indonesian society are problems that must be resolved immediately. The wealth of abundant natural resources and the total population of Indonesia around 278 million people should be a strong capital to advance the economy, both as producers and consumers. The Qur'an views that poverty is a social problem that must be alleviated. Everyone, especially Muslims, is challenged to be harder at work and entrepreneurship (entrepreneurship) to be more professional in managing the potentials and real strengths of the people's economy. Therefore, in addition to mastery of lifeskills or life skills, more real and urgent entrepreneurial skills are needed in the development and empowerment of the people's economy and providing opportunities to the people to go down (small). However, it is very unfortunate that people's economic empowerment and the provision of opportunities have received less attention, economic development and empowerment have so far only been enjoyed by the upper middle class. As a result, it is the economic inequality that is increasingly visible. The purpose of this study is to find out 1). The economic problems of the people in the current era; 2). Quranic conception of economic empowerment; 3). Reviving the People's Economy: Fostering a Spirit of Independence And Entrepreneurship in the Modern Era. This type of research is descriptive-analytical, the research method used is field research (field research). The results showed that the problems that are being faced in the economic empowerment of the people in the modern era are the high consumptive culture of the community, entrepreneurship education in Indonesia is still in the weak category, and the mindset of becoming a Civil Servant (PNS). In shaping the character of independence and entrepreunership of the Indonesian nation, namely building a solid foundation of faith, good leadership and management, daring to face risks, and building an entrepreneurial and independent mentality from an early age.